KESIAPAN GURU PAI DALAM MELAKSANAKAN KEBIJAKAN KURIKULUM MERDEKA DI SMP LTI IGM PALEMBANG - Rara Yurisia; karoma Karoma; Tutut Handayani; Muhammad Fauzi (Sekolah Tinggi Agama Islam Raudhatul Ulum, 2023)
Abstract, This research is motivated by how prepared Islamic Religious Education teachers are in implementing the Merdeka curriculum. Data collection techniques used are observation, interviews, and documentation. While technical data analysis includes: data reduction, data presentation, data verification, and data triangulation. The results of this study indicate that Islamic Religious Education teachers in Indo Global Mandiri Palemabang Life Skill Technology Junior High School are generally ready to implement the Merdeka curriculum, starting from readiness for New Student Admissions (PPDB), readiness to prepare a Brief Lesson Implementation Plan (RRP) format, Assessment in lieu of National Standard School Examination (USBN), and Minimum Competency Assessment (AKM) and Character Survey.